Weather Condition Monitoring System as A Floods Prevention in Malang using Android Application - Audia Yumna Dita Pramesti; Farida Arinie Soelistianto; Lis Diana Mustafa (Politeknik Negeri Malang, 2022)
On January 2021 rain often splashing Malang City with intensity high and deep period a long time, so some areas experience flood. BMKG is an Indonesian official institution in charge to give information forecast weather good through online media nor offline. However, they do not give specific information about real-time location weather. This study aims to make it easy for user in accept information on bulk rain, water level, wind speed and temperature as effort to prevent flood. This study proposed prototype using bulk sensor rain, water level, wind speed and temperature as well as using ESP32 as microcontroller with monitoring via android. This tool could put in general place or in a vulnerable flood area. Results show that sending data from ESP32 microcontroller to firebase database is successful sent through